Interleukin-15 enhances natural killer cell cytotoxicity in patients with acute myeloid leukemia by upregulating the activating NK cell receptors - Szczepanski, Miroslaw J. (Springer-Verlag, 2009)
Interleukin-15 (IL-15) has a major role in NK-cell homeostasis. Modulation of the relative frequency and expression intensity of the NK-cell receptors by IL-15 may increase NK cell-mediated cytotoxicity in cancer patients. We investigated the receptor repertoire and measured NK-cell activity in newly diagnosed AML patients and evaluated the ex vivo effects of IL-15. The expression of the activating NK cell receptors was significantly decreased in the AML patients compared to that in NK cells of healthy donors. When NK cells obtained from AML patients were cultured with IL-15, expression of the activating receptors was significantly upregulated compared to pre-culture levels. Concomitantly, cytotoxic activity of NK cells against autologous leukemic blasts increased following IL-15 stimulation. This IL-15 induced increase in activity was blocked by neutralizing antibodies specific for the NK cell activating receptors. These pre-clinical data support the future use of IL-15 for NK cell- based therapies for AML patients.